1975
DOI: 10.1177/014616727500100312
|View full text |Cite
|
Sign up to set email alerts
|

Core Body Temperature and Social Arousal

Abstract: Arousal can be thought of as basic metabolic activity, which produces heat. Considerable metabolic activity takes place in the brain. Temperature measured at the tympanic membrane (eardrum) is highly correlated with core temperature at the hypothalamus and may provide an index of arousal. In two experiments tympanic temperature was observed to increase during social interaction. Temperature increased less with three partners than with one, possibly due to the diffusion of attention from others.The concept of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1977
1977
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Increases in term perature are not subject to the same limit and are in general much larger (cf. Dabbs & Moorer. 1975).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increases in term perature are not subject to the same limit and are in general much larger (cf. Dabbs & Moorer. 1975).…”
Section: Discussionmentioning
confidence: 99%
“…We suspect the occasional increases we observed were associated with feelings of anxiety and a failure to concentrate, but perhaps they would appear under any conditions of general arousal. Others report that unexpected interaction with a stranger leads to increases in temperature among animals (von Saint Paul & Aschoff, 1968) and among people (Dabbs & Moorer, 1975). Using telemetry, we plan to explore further the conditions that cause temperature to increase.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore a conclusion can be drawn that a quarantine significantly affects the values of the happiness, valence and sadness variables. Dabbs and Moorer (1975) found that an index of arousal can be provided by human core temperature. A new marker of emotional arousal is functional infrared thermal imaging, which promises to become a method for measuring autonomic emotional responses via facial, cutaneous, thermal variations .…”
Section: The Artificial Intelligence Cluster Analysismentioning
confidence: 99%
“…Their study regarded the mean measurement of musical intensity that could compare to arousal. These scholars believed that there were highly comparable characteristics between the arousal dimension and a measurement of their intensity.Yet, different scholars(Dabbs and Moorer, 1975, Zenju et al, 2002, Zenju et al, 2004, Salazar-López et al, 2015, Kosonogov et al, 2017) conducting research expressed different opinions regarding how human arousal and temperature correlated.…”
mentioning
confidence: 99%